OCTREOTIDE'NİN YENİDOĞAN STREPTOZOTOCIN DİYABETİK SIÇAN BÖBREĞİ VE IGF-1 DÜZEYLERİ ÜZERİNE ETKİLERİ - TUNÇDEMİR, Matem; ÖZTÜRK, Melek (Cerrahpaşa Medical Journal, 2019)
Background and Design.- It has been shown by the studies that somatostatin and its analogues (octreotide) have a useful effect on the treatment of diabetes and its complications. In this study 4 groups of newborn Wistar rats were prepared. 1st and 2nd Group; Neonatal STZ (n-STZ)-diabetic group (100 mg/kg, single dose, i.p. on the second day of birth). 2nd Group; Octreotide treated n-STZ-diabetic group ( 200 µg/kg/day, i.p, from 12.week to 18.week ). 3rd Group; Octreotide treated non diabetic group ( 200 µg/kg/day,i.p., from 12.week to 18.week). 4.Group; Control group. In all STZ treated groups (1st ,2nd group) while a significant increase in the blood glucose compared to healty controls until 12th week. Results.- A decrease in the blood glucose levels of octreotide treated diabetic group have been observed. Kidney weights were increased in STZ diabetic groups compared to healty control groups. A significant increase in octreotide treated diabetic groups was determined. Serum IGF-1 levels were found decreased in octreotide treated diabetic group. Glomerule sizes increased in STZ diabetic groups compared to controls. There were basal membrane thickening and significant increase in mesangial matrix and mesangial cells in the diabetic groups. Renal tissue IGF-1 immunoreactivity on the kidney tubules of the control group was found higher than the diabetic group. IGF-1 immunosreactivity was generally seen on the glomerules of the STZ-diabetic group. In Octreotide treated nSTZ-diabetic group weaker IGF-1 immunreaction observed at glomerules and tubules compared to nSTZ-diabetic and healthy control group. The microalbuminuria levels of the treated diabetic group were found reduced when compared with the diabetic group. Conclusion.- We observed that the dose of octreotide and the period has an important contribution for preventation and improvement of nephropathy and prevent the renal tissue damage. on the newborn STZ-diabetic rats.